Motor neuron degeneration due to aluminium deposition in the spinal cord: a light microscopical study - (:unkn) unknown (URBAN & FISCHER VERLAG, 1999)
For a long time, aluminium has been considered as an indifferent element from a toxicological point of view. In recent years, it became clear that aluminium is a potential toxic agent in humans and has been implicated in the pathogenesis of several clinical disorders, such as dementia, respiratory tract disorders and allergic reactions. Chronic exposure to aluminium fumes, inhalation of aluminium and aluminium-oxide powder increase the risk to develop serious central nervous system pathology, in particular Alzheimer's disease and amyotrophic lateral sclerosis (ALS). In the present study, 3 experimental and 1 control group of rats were used to study the effects of aluminium on the central nervous system. Aluminium was injected intracisternally as a single dose (50 mu g for group I, 100 mu g for group II and 300 mu g for group III) to the experimental groups (n = 5 in each group). The same dose was given at 3 months after the first injection to all groups. The control group (n = 5) was intracisternally given a physiological salt solution. Electromyography (EMG) was applied to the rats of the experimental groups. Rats were decapitated at 3 months after the second injections. Spinal cord samples from lombar and cervical regions were removed and histological examination was performed. Light microscopical investigations revealed severe degeneration in motor neurons of the rats treated with 300 mu g. Neurofibrillary tangle formation, chromatolysis and abnormal localization of the nuclei were found in swollen perikarya. Extreme loss of motor neurons with ghost cell appearance was found in that group. Sections of spinal cords of rats treated with lower doses of aluminium showed a moderate degree of motor neuron damage. EMGs of rats treated with the high dose of aluminium revealed severe acute denervation whereas treatment with lower doses resulted in moderate denervation. We conclude that aluminium may cause severe motor neuron damage in rat spinal cord resembling ALS.
Keywords: motor neuron; histology; aluminium; amyotrophic lateral sclerosis; toxicology; neurological disorder; PATHOLOGY